Effects of ML-236B (Compactin) on Sterol Synthesis and Low Density Lipoprotein Receptor Activities in Fibroblasts of Patients with Homozygous Familial Hypercholesterolemia - Haba, Toshihiro (1981)
We studied biochemical genetics of low density lipoprotein (LDL) receptor mutations in fibroblasts from six homozygous and five heterozygous patients with familial hypercholesterolemia (FH). Three of six homozygotes are receptor-negative type and the other three homozygotes are receptor-defective type. In the cells from three receptor-negative homozygotes, the receptor binding, internalization, and degradation of (125)I-LDL were 0.5±0.3 ng/mg protein (mean±SEM), 14±8 and 8±6 ng/mg protein per 6 h (four normal cells; 44±3, 386±32, and 1,335±214 ng/mg protein per 6 h), respectively. In the cells from three receptor-defective homozygotes, the receptor binding, internalization, and degradation of (125)I-LDL were 6±2, 29±8, and 90±32 ng/mg protein per 6 h, respectively. In these six homozygotes, two pairs of siblings are included. Two siblings in the same family were classified as receptor-negative and two siblings in another family were classified as receptor-defective. The receptor-negative phenotypes and the receptor-defective phenotypes bred true in individual families. The cells from five heterozygotes showed ∼46% of the normal activities of receptor. ML-236B, competitive inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA reductase), completely inhibited the incorporation of [(14)C]acetate into digitonin-precipitable sterols in fibroblasts from normal subjects and heterozygous and homozygous patients with FH with the concentration of 0.5 μg/ml. However, at 0.05 μg/ml of ML-236B sterol synthesis in fibroblasts from homozygotes was not completely suppressed in contrast to normal and heterozygous cells. Moreover, after preincubation with 0.05 μg/ml of ML-236B for 24 h in medium containing lipoproteins, sterol synthesis in the cells from receptor-negative homozygote showed 75% of the initial activity compared with that of 25% without preincubation. In the cells from a normal subject and a heterozygote, sterol synthesis was inhibited even after preincubation. These results suggest that (a) the inhibitory effect of ML-236B is overcome in homozygote cells by their high intracellular levels of HMG-CoA reductase and (b) that a higher dose of ML-236B may be required to lower serum cholesterol levels in FH homozygotes than in heterozygotes.